2006
DOI: 10.1097/01.ccm.0000201407.89977.ea
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atorvastatin on systemic inflammatory response after coronary bypass surgery

Abstract: Pretreatment with atorvastatin significantly reduces cytokine release and neutrophil adhesion to the venous endothelium in patients undergoing coronary artery bypass grafting with cardiopulmonary bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
177
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(183 citation statements)
references
References 34 publications
3
177
1
2
Order By: Relevance
“…The two previous meta-analyses 9 10 contained data on seven trials, [19][20][21][22][23][24][25] yielding a total of 3608 randomised patients and about 1050 person years of follow-up (0. 3 years per patient).…”
Section: Shorter Term Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two previous meta-analyses 9 10 contained data on seven trials, [19][20][21][22][23][24][25] yielding a total of 3608 randomised patients and about 1050 person years of follow-up (0. 3 years per patient).…”
Section: Shorter Term Trialsmentioning
confidence: 99%
“…Tamayo et al 28 Chello et al 23 Ozaydin et al 24 Xia et al 30 Garcia-Fernandez et al 25 Dernellis et al 21 Song et al 26 Tveit et al 19 Ji et al 31 Mannacio …”
Section: Shorter Term Trials (Published Only)mentioning
confidence: 99%
“…Studies have shown that statins reduce neutrophil influx in the lung which might have a strong effect on attenuating the downstream inflammatory events, such as macrophage influx, lymphocyte activation and inhibition of cytokine release, in particular IL-8 that appears central to the neutrophil inflammation of the lung [67][68][69][70][71][72][73][74][75][76][77][80][81][82][83][84][85][86][87][88]. The inhibition of IL-6, IL-8 and GM-CSF expression by statins has been shown in cell cultures of human BEC [65,70].…”
Section: Statin Effects On Pulmonary Inflammation In Copdmentioning
confidence: 99%
“…44 Finally, we found that preoperative statin use was associated with a 60% risk reduction in POAF incidence. The antiarrhythmic mechanism of statins can possibly be explained by their effects on inflammation 45,46,47,48 , antioxidant effects 49,50 , antiarrhythmic effects due to ion channel stabilization 51 , a role in extracellular matrix modulation 52 , an inhibition of synthesis of isoprenoids that are significant for the posttranslational modification of such signalling molecules as Rho, Rac, and Ras…”
Section: Discussionmentioning
confidence: 99%